Hubungan antara Religiositas dengan Perilaku Bullying pada Pemuda Gereja di Salatiga - Jenny Erine Valentina; Ratriana Yuliastuti Endang Kusumiati (Psyche 165 Journal, 2022)
There is a phenomenon in Salatiga city where bullying is done by the church youth. Bullying is a repeated act of hurting others physically, verbally, or relationally. The church youth are in the early adulthood stage which is a critical period and has the potential for deviant behavior. The emergence of this problem and behavior is completely irrelevant to Christian teaching. Essentially, every church youth has been equipped with religious values. However, some still do bullying or behave negatively towards others. This study aims to determine the connection between religiosity and bullying behavior from the church youth in Salatiga. The measurement of this research uses The Centrality of Religiosity Scale (CRS) and Revised Olweus Bully/Victim Questionnaire (OBVQ-R). In the study, the number of participants are 50 people according to predetermined criteria. The data is obtained by distributing an online questionnaire (Likert scale) via google form. Using Spearman's Rho Correlations to analyze the data. The result shows that there is no negative connection between religiosity and bullying behavior in the church youth in Salatiga. The correlation coefficient value is 0.055 with a significance value of 0.351 (P>0.05).